Characterization of Commercial Solid Waste Stream in Bayelsa State, Nigeria - C.N Angaye, Tariwari; Konmeze, Odigo; A. Gbodo, Endurance; Apollos, Ubi (Journal of Experimental and Clinical Toxicology, 2019)
The problem associated inappropriate management of municipal waste to the ecosystem cannot be overemphasized. This study involved the physical characterization of municipal solid waste streams in 4 commercial dumpsites in Yenagoa Metropolis, using the quartile estimate method. Results showed that out of a total mass of 79.82kg; the individual mass composition was reported for garbage (food) waste 33.32 (39%), paper waste 14.90 kg (40.82%), plastic waste 5.12 kg (6%), nylon 11.01kg (13%), metal 4.31 kg (5%), wood 2.29 kg (3%), electronic 5.69 kg (7%), glass/ceramic 3.48 kg (4%) and unclassified waste whose mass was 4.62kg (5%). Disposal of untreated and unsegregated/uncharacterized waste adverse effect to the environment. It is hereby recommended that the populace to desist from illicit disposal of waste stream. In addition all stakeholders and Government in particular should formulate policies the reduction, reuse and recycling of waste stream.
Keywords: Commercial waste; characterization; Recycling; waste streams